2020
DOI: 10.3389/fmats.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Form of Standard Linear Solid Model for Characterizing Stress Relaxation and Creep: Including a Novel Parameter for Quantifying the Ratio of Fluids to Solids of a Viscoelastic Solid

Abstract: The standard linear solid model (SLSM) is a typical and useful model for analyzing stress relaxation and creep behaviors of viscoelastic solids for obtaining the corresponding viscoelastic properties. However, the analysis results cannot be directly compared to the parameters commonly adopted for defining the mechanical properties of viscoelastic solids in the finite element simulation package such as the modulus of elasticity (E e) and the two parameters in the dimensionless form of the relaxation modulus (g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The error for becomes significant (higher than 5%) for the fourth case in the second group when is 0.9. In [ 35 ], it was found that the error of the estimation of viscoelastic time constants increased nonlinearly with increasing , and became larger and larger when was larger than 0.9 and approached 1. The possible reason for this phenomenon is that numerical divergence can occur and get larger when approaches its upper limit 1, causing the distortion of the simulated strain–time curve and resulting in a significant error.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The error for becomes significant (higher than 5%) for the fourth case in the second group when is 0.9. In [ 35 ], it was found that the error of the estimation of viscoelastic time constants increased nonlinearly with increasing , and became larger and larger when was larger than 0.9 and approached 1. The possible reason for this phenomenon is that numerical divergence can occur and get larger when approaches its upper limit 1, causing the distortion of the simulated strain–time curve and resulting in a significant error.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that [ 35 ], in the standard linear solid model, there is a physical parameter defined as: where is a real number between 0 and 1. The physical meaning of is associated with the ratio of viscous fluids to solids in a viscoelastic solid [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations